Tumor‐infiltrating FoxP3+ T cells are associated with poor prognosis in oral squamous cell carcinoma - Tomio Hayashi; Kazuhiro Yoshikawa; Susumu Suzuki; Masahiko Gosho; Ryuzo Ueda; Yoshiaki Kazaoka (Wiley, 2022)
Abstract Objectives Squamous cell carcinoma is the most common malignancy in the oral cavity. Moreover, human papillomavirus (HPV) infection has been recently implicated in the onset of oral squamous cell carcinoma (OSCC). Regulatory T cells (Tregs) are Forkhead box P3 (FoxP3) positive and are normally involved in the mechanism by which organisms escape attacks from their own immune system; however, in tumors, these cells are known to suppress antitumor immunity and block the attack against tumors. The present study evaluated the associations of the number of Tregs and HPV infection with prognoses in patients with OSCC. Material and methods Samples from 106 patients diagnosed with OSCC were evaluated by immunohistochemical staining for the identification of FoxP3+ Tregs and HPV. The relationship between the observed number of Foxp3‐positive cells, the presence/absence of HPV infection and associations with clinicopathological indicators were analyzed. Results Tissues were classified into high (High) and low (Low) Treg count groups, with 69 patients classified as High and 37 classified as Low. The prognoses were significantly better in the Low group compared with the High group (p = 0.04). FoxP3 expression may have had some effect on nodal metastases (p = 0.09). HPV antigens were detected in 65 patients, but there were no significant associations with prognosis (p = 0.34). HPV‐infected tumors were more common in the gums and tongues than in the lips, cheeks, and floor of the mouth (p = 0.05). Conclusions These results indicate that Tregs in tumor sites are associated with worsened prognoses of patients with OSCC and suggest potential therapies targeting Tregs in OSCC.